Structure and Dynamics of the Bacterial Flagellar Motor Complex - Shuichi Nakamura; Tohru Minamino (Biomolecules)
Many bacteria swim in liquids and move over solid surfaces by rotating flagella. The bacterial flagellum is a supramolecular protein complex that is composed of about 30 different flagellar proteins ranging from a few to tens of thousands. Despite structural and functional diversities of the flagella among motile bacteria, the flagellum commonly consists of a membrane-embedded rotary motor fueled by an ion motive force across the cytoplasmic membrane, a universal joint, and a helical propeller that extends several micrometers beyond the cell surface. The flagellar motor consists of a rotor and several stator units, each of which acts as a transmembrane ion channel complex that converts the ion flux through the channel into the mechanical work required for force generation. The rotor ring complex is equipped with a reversible gear that is regulated by chemotactic signal transduction pathways. As a result, bacteria can move to more desirable locations in response to environmental changes. Recent high-resolution structural analyses of flagella using cryo-electron microscopy have provided deep insights into the assembly, rotation, and directional switching mechanisms of the flagellar motor complex. In this review article, we describe the current understanding of the structure and dynamics of the bacterial flagellum.